Penerapan Media Pembelajaran Visual Papan Pecahan pada Mata Pelajaran Matematika Materi Pecahan DI Kelas IV SD Negeri 105365 Lubuk Bayas - Siti Hadijah; Rustam; Lailatun Nur Kamalia Siregar (eductum: Jurnal Literasi Pendidikan, 2023)
Study aims to observe how the teacher uses learning media in using visual media in learning Mathematics at IV SD Negeri 105365 Lubuk Bayas, the supporting factors and inhibiting factors faced by teachers in using visual media in learning Mathematics for class IV SD Negeri 105365 Lubuk Bayas. This research is a type of This qualitative research and uses a descriptive qualitative approach. The data was obtained through several data sources, namely observation, interviews, and supporting documentation of visual learning media, the availability of textbooks and the activeness of SD Negeri 105365 Lubuk Bayas teachers in participating in training related to learning media. While the inhibiting factors faced by teachers are 3 factors, namely the availability of time in providing visual media, the need for quantity additions and updates related to supporting tools for visual learning media and the availability of textbooks that can support Mathematics learning activities. Students' perceptions of learning activities that use visual media in Indonesian language learning class IV SD Negeri 105365 Lubuk Bayas, namely students giving positive responses. Students like and feel happy and do not feel bored when the teacher teaches using a variety of visual media. Students hope that learning with visual media will continue to be carried out and students hope that in the future learning can also be done outside the classroom to make it even more enjoyable.